Concepts of Fitness and Wellness - Flynn, Scott; Jellum, Lisa; Howard, Jonathan; Moser, Althea; Mathis, David; Collins, Christin; Henderson, Sharryse; Watjen, Connie; Open Textbook Library (Open Textbook Library, 2018)
This open textbook for Concepts of Fitness and Wellness at Georgia Highlands College was created through a Round Seven ALG Textbook Transformation Grant.
1. Healthy Behaviors -- 2. Fitness Principles -- 3. Cardiorespiratory Fitness -- 4. Muscular Fitness -- 5. Flexibility -- 6. Body Composition -- 7. Nutrition -- 8. Weight Management -- 9. Stress -- 10. Cardiovascular Disease -- 11. Cancer -- 12. Substance Use and Abuse -- 13. Sexually Transmitted Infections
In English.
Description based on online resource
Keywords: Science -- Textbooks; Biology -- Textbooks; Medicine -- Textbooks